Mixed Cationic Surfactant Vesicles in (Dioctadecyldimethylammonium Bromide)/NaCl and (Dioctadecyldimethylammonium Chloride)/NaBr Aqueous Dispersions - Feitosa, Eloi [UNESP]; Lemos, Monique [UNESP]; Adati, Renata D. (Wiley-Blackwell, 2019)
One of the most challenging characteristics not fully understood yet of the cationic surfactant salt dioctadecyldimethylammonium (DODA(+)) halide is concerned with the effects of the counterion (usually Br- and Cl-) on the surfactant assembly into vesicle structures in aqueous solution. These counterions play a key role in the self-organization of DODA(+) into bilayer structures. Differential scanning calorimetry (DSC) and dynamic light scattering (DLS) techniques were used here to investigate systematically the effects of the single salts NaCl and NaBr, respectively, on the thermal behavior and structural organization of the cationic dioctadecyldimethylammonium bromide and chloride (DODAB and DODAC) in water. The results undoubtedly indicate that the added Br- or Cl-, respectively, into DODAC and DODAB aqueous dispersions, replaces partially the bound counterions (Cl- and Br-) from the vesicles, yielding formation of DODAB/DODAC mixed vesicles. As a conclusion, single salts may be used to tune the thermal and structural characteristics of cationic vesicles.
Keywords: DODAB; DODAC; Cationic surfactant vesicles; Counterion; Thermal behavior